CH4 isotopic signatures of emissions from oil and gas extraction sites in Romania - Menoud, Malika; van der Veen, Carina; Maazallahi, Hossein; Hensen, Arjan; Velzeboer, Ilona; van den Bulk, Pim; Delre, Antonio; Korbeń, Piotr; Schwietzke, Stefan; Ardelean, Magdalena; Calcan, Andreea; Etiope, Giuseppe; et al. (Elementa, 2022)
Methane (CH4) emissions to the atmosphere from the oil and gas sector in Romania remain highly uncertain despite their relevance for the European Union’s goals to reduce greenhouse gas emissions. Measurements of CH4 isotopic composition can be used for source attribution, which is important in top-down studies of emissions from extended areas. We performed isotope measurements of CH4 in atmospheric air samples collected from an aircraft (24 locations) and ground vehicles (83 locations), around oil and gas production sites in Romania, with focus on the Romanian Plain. Ethane to methane ratios were derived at 412 locations of the same fossil fuel activity clusters. The resulting isotopic signals (δ13C and δ2H in CH4) covered a wide range of values, indicating mainly thermogenic gas sources (associated with oil production) in the Romanian Plain, mostly in Prahova county (δ13C from -67.8 ± 1.2 to -22.4 ± 0.04 ‰ Vienna Pee Dee Belmnite; δ2H from -255 ± 12 to -138 ± 11 ‰ Vienna Standard Mean Ocean Water) but also the presence of some natural gas reservoirs of microbial origin in Dolj, Ialomiţa, Prahova, and likely Teleorman counties. The classification based on ethane data was generally in agreement with the one based on CH4 isotopic composition and confirmed the interpretation of the gas origin. In several cases, CH4 enhancements sampled from the aircraft could directly be linked to the underlying production clusters using wind data. The combination of δ13C and δ2H signals in these samples confirms that the oil and gas production sector is the main source of CH4 emissions in the target areas. We found that average CH4 isotopic signatures in Romania are significantly lower than commonly used values for the global fossil fuel emissions. Our results emphasize the importance of regional variations in CH4 isotopes, with implications for global inversion modeling studies.